2017
DOI: 10.1016/j.anbehav.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Mate choice intensifies motor signalling in Drosophila

Abstract: Mate choice has the potential to act on the evolution of motor performance via its direct influence on motor sexual signals. However, studies demonstrating this are rare. Here, we perform an in-depth analysis of Drosophila pseudoobscura courtship song rate, a motor signal under mate choice in this species, and analyse the response of this signal to sexual selection manipulation using experimental evolution. We show that manipulating the opportunity for sexual selection led to changes in song production rate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 84 publications
0
24
2
Order By: Relevance
“…However, increased burst length during courtship will result in more song per unit time, which seems likely to increase the stimulatory effect of song on females and thus the copulation success of males that produce longer bursts. Consistent with this, male D. pseudoobscura experimentally evolved under heightened sexual competition increase the amount of song they can sustain during active courtship (Debelle, Courtiol, Ritchie, & Snook, ). Also, D. melanogaster males produce shorter burst lengths of songs when courting females in the presence of other males (Tauber & Eberl, ), suggesting that males may modulate their singing efforts in opposing ways depending on whether the competition with other males is direct or not.…”
Section: Discussionmentioning
confidence: 69%
“…However, increased burst length during courtship will result in more song per unit time, which seems likely to increase the stimulatory effect of song on females and thus the copulation success of males that produce longer bursts. Consistent with this, male D. pseudoobscura experimentally evolved under heightened sexual competition increase the amount of song they can sustain during active courtship (Debelle, Courtiol, Ritchie, & Snook, ). Also, D. melanogaster males produce shorter burst lengths of songs when courting females in the presence of other males (Tauber & Eberl, ), suggesting that males may modulate their singing efforts in opposing ways depending on whether the competition with other males is direct or not.…”
Section: Discussionmentioning
confidence: 69%
“…For example, mutants of members of the pickpocket family in D. melanogaster show aberrant male mating success because of their involvement in the detection of female pheromones (Thistle et al, 2012;Toda et al, 2012). E males, subject to both intra-and intersexual selection, have diverged in aspects of courtship behaviour, such as time until initiation of courtship, have a higher intensity courtship song and have a higher competitive mating success than M males (Debelle et al, 2016;Debelle et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of these lines have found divergence in some, but not all, of the types of traits predicted to diverge under sexual selection. Sperm morphology and heteromorphism, and testis mass did not diverge, but E males had larger accessory glands and a greater mating capacity (Crudgington et al, 2009), were more competitive in mating encounters (Debelle et al, 2016), and produced more attractive courtship song than M males (Debelle et al, 2017). Coevolutionary changes have occurred in female song preferences (Debelle et al, 2014 ).…”
Section: Introductionmentioning
confidence: 94%
“…Regardless of said difficulties, numerous experimental evolution studies, where populations are exposed to a controlled laboratory environment for some number of generations (Kawecki et al, 2012), have made remarkable discoveries on the genomic architecture of adaptation. Examples of long-term experimental evolution studies include those on yeast (Burke et al, 2014), red flour beetles (Godwin et al, 2017) and fruit flies (Turner et al, 2011; Debelle et al, 2017). By combining experimental evolution with next-generation sequencing, Evolve-and-Resequence studies (E&R, fig.…”
Section: Introductionmentioning
confidence: 99%